The relationship between technological changes and computer anxiety among employees in banking sectors / Maimunah Mohd Shah - Mohd Shah, Maimunah (2013)
The growing role of computers and technology in the workplace has changed the office landscape dramatically and necessitated employees to be competent and knowledgeable in order to manage computers effectively. Nevertheless, this adaptation to technology creates anxiety prompting much research in the area particularly focusing on schools, universities and younger or elderly adults. Research into computer anxiety experienced in commercial organisations has been much neglected. This study fills this gap by examining and determining the level of computer anxiety, attitude towards computers and technology acceptance among employees in commercial banks. Survey data gathered from 377 employees in various commercial banks in Kuala Lumpur was used to compare relationships between the stated variables and to assess if demographic characteristics like gender and job category played a moderating role in such relationships. Results show that the Cronbach’s Alpha scores for all the variables were valid and acceptable. T-tests and Anova tests were conducted on computer anxiety and demographic profile of the respondents showed there are differences among the items tested. Analysis of correlations revealed significant negative relationships between computer anxiety and technology acceptance, computer skills, computer knowledge, computer applications and attitude towards computers. The multiple regressions analysis indicates that the most efficient model for explaining computer anxiety was computer skills, technology acceptance and computer knowledge. The research contributes to better understanding of bank employees’ anxiety and resistance to technology. This holds practical and managerial implications. To reap benefits from technological implementation at the workplace, practitioners must ensure that such implementations are well understood and that unskilled staff are trained and given greater management and technical support.